STANDARISASI SIMPLISIA DAUN KELOR (Moringa oleifera L.) DARI DESA LUWUNG SIDOARJO DENGAN MENGGUNAKAN PENGERINGAN FOOD DEHYDRATOR - MELLA NUR AZIZAH; ARISTA WAHYU NINGSIH; BUTET SINAGA (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2022)
One of the vegetation that may be used each as meals and medication is the Moringa plant (Moringa oleifera L.). Empirically, Moringa leaves have many advantages and had been proven to be powerful in treating numerous diseases, consisting of diabetes, hepatitis, heart ailment and excessive cholesterol. The chemical parts contained on this plant are terpenoids, tannins, steroids, polyphenols, and alkaloids. This look at aims to pick out medicinal uncooked substances the use of the meals dehydrator drying method whilst on the equal time making sure the drug raw materials, so that the standardization can be accounted for for its quality. Standardization is done by setting specific and non-specific parameters. This study uses descriptive qualitative and quantitative analysis methods. The sample of this research was taken from Luwung village, Sidoarjo regency. The results of standardization for specific parameters showed the determination of the flavonoid content of 16,08±3,62 mgQE/g, the TLC test showed stains in the form of yellow-green fluorescence under UV light at 366 nm, the water-soluble extract test yielded 7.8%, and the water-soluble extract test yielded 7.8%. ethanol yielded 13.58%. The results for non-specific parameters showed that drying shrinkage was 4.2%, water content was 1.80%, and ash content was 1.4%. The results of the microbial contamination test were 3.9x colonies/ml while the total mold/yeast contamination was 3.1x colonies/ml. Based at the results of studies that has been carried out, Moringa leaf simplicia from Luwung village has met the requirements of specific and non-specific parameters, so that the simplicia may be used as raw material for medication.